TNF-α Induces Epithelial–Mesenchymal Transition of Renal Cell Carcinoma Cells via a GSK3β-Dependent Mechanism - Ming-Yi Ho; Shye-Jye Tang; Mei-Jen Chuang; Tai-Lung Cha; Jing-Yao Li; Guang-Huan Sun; Kuang‐Hui Sun (2012)
TNF-α is a cytokine with antitumorigenic property. In contrast, low dose, chronic TNF-α production by tumor cells or stromal cells may promote tumor growth and metastasis. Serum levels of TNF-α are significantly elevated in renal cell carcinoma (RCC) patients. Here, we showed that TNF-α induced epithelial-mesenchymal transition (EMT) and promoted tumorigenicity of RCC by repressing E-cadherin, upregulating vimentin, activating MMP9, and invasion activities. In addition, TNF-α treatment inhibited glycogen synthase kinase 3β (GSK-3β) activity through serine-9 phosphorylation mediated by the phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathway in RCC cells. Inhibition of PI3K/AKT by LY294002 reactivated GSK-3β and suppressed the TNF-α-induced EMT of RCC cells. Inactivation of GSK-3β by LiCl significantly increased MMP9 activity and EMT of RCC cells. Activation of GSK-3β by transduction of constitutively active GSK-3β into RCC cells suppressed TNF-α-mediated anchorage-independent growth in soft agar and tumorigenicity in nude mice. Overexpression of a kinase-deficient GSK-3β, in contrast, potentiated EMT, anchorage-independent growth and drastically enhanced tumorigenicity in vivo. Most importantly, a 15-fold inactivation of GSK-3β activity, 3-fold decrease of E-cadherin, and 2-fold increase of vimentin were observed in human RCC tumor tissues. These results indicated that inactivation of GSK-3β plays a pivotal role in the TNF-α-mediated tumorigenesis of RCC.